The impact of the COVID-19 pandemic on the decrease in the use of intensive care units in the postoperative period of anatomic lung resections. A retrospective analysis - DIAS,ISMAEL RODRIGO (2022)
ABSTRACT Objective: COVID-19 pandemic required optimization of hospital institutional flow, especially regarding the use of intensive care unit (ICU) beds. The aim of this study was to assess whether the individualization of the indication for postoperative recovery from pulmonary surgery in ICU beds was associated with more perioperative complications. Method: retrospective analysis of medical records of patients undergoing anatomic lung resections for cancer in a tertiary hospital. The sample was divided into: Group-I, composed of surgeries performed between March/2019 and February/2020, pre-pandemic, and Group-II, composed of surgeries performed between March/2020 and February/2021, pandemic period in Brazil. We analyzed demographic data, surgical risks, surgeries performed, postoperative complications, length of stay in the ICU and hospital stay. Preventive measures of COVID-19 were adopted in group-II. Results: 43 patients were included, 20 in group-I and 23 in group-II. The groups did not show statistical differences regarding baseline demographic variables. In group-I, 80% of the patients underwent a postoperative period in the ICU, compared to 21% in group-II. There was a significant difference when comparing the average length of stay in an ICU bed (46 hours in group-I versus 14 hours in group-II - p<0.001). There was no statistical difference regarding postoperative complications (p=0.44). Conclusions: the individualization of the need for ICU use in the immediate postoperative period resulted in an improvement in the institutional care flow during the COVID-19 pandemic, in a safe way, without an increase in surgical morbidity and mortality, favoring the maintenance of essential cancer treatment.